Influence of system, information and digital payment qualities on customer satisfaction of gojek super app - Adisthy Shabrina Nurqamarani; Faizal Reza; Nur Fitriani; Eka Yudhyani; Andi Indrawati (Faculty of Economics and Business Mulawarman University, 2022)
In the era where technology and big data play the key role in determining success, a lot of startups emerged utilizing the opportunities to grab market, Gojek is one of the successful startups which claimed itself as the first super-app in the world. Despite its claim, Gojek faces intense competition with Grab, another super-app in Indonesia, and therefore ensuring qualities in its application hold important role to determine customer satisfaction to maintain the market. This study aims to analyze the effect of qualities attributes of system, information, and digital payment on customer satisfaction of Gojek Super Application through a sample of 100 respondents which were selected through purposive sampling method. The result revealed that system, information, and digital payment quality affected customer satisfaction significantly both partially and simultaneously. This research recommends Gojek to evaluate the service quality in its super app by considering the qualities of system, information and digital payment to improve customer satisfaction.